(untitled) (CAHIERS MAGELLANES-NS, 2024)
Annotation: This article is aimed at clarifying the role of dictation in the development of students' written speech, it is explained through the method of "dictation and music" harmony and its experimental results. The article describes the method of obtaining the "dictation and music harmony" method and the factors affecting the development of written speech of primary school students in general secondary schools.